Kombinasi Metode Analytical Hierarchy Process (AHP) dan Multi- Attribute Utility Theory (MAUT) Pada Lomba Balita Sehat Untuk Usia 6- 24 Bulan - Heliza Rahmania Hatta; Boby Pradana; Dyna Marisa Khairina (Prosiding SISFOTEK, 2020)
The competition for healthy toddlers is one of the activities to improve public awareness of children's health. Healthy Toddler competition in Puskesmas Remaja, Samarinda, East Kalimantan, has two categories of valuation, i.e. group of age 6 to 24 months and a group of ages 2 to 5 years. Both categories have considerable assessment criteria so that the calculations are effective and efficient so that the competition can run precisely and quickly as expected. During this time, the collected data is still in paper form so it needs a good and safe storage place. This Puskesmas Remaja has often experienced flooding so that many papers (data) are damaged because of flooded flooding. Therefore, a decision support system is required that can help Puskesmas Remaja in conducting calculations for healthy toddler competitions as well as in the storage of the competition data. The system is built using a combination of Analytical Hierarchy Process (AHP) and Multi-attribute Utility Theory (MAUT). The system generates the priority of weights using the AHP method and results of the evaluation of the competition in the form of the method of MAUT. The system uses 27 criteria and 19 alternate data participants in healthy toddlers competition in the group age 6 to 24 months, the system generates an accuracy of 73.68%.